Efektivitas Metode Diskusi Dalam Pembelajaran Kitab Kuning Terhadap Kepribadian Santri Di Pondok Pesantren - Ach Khusnan (Program Studi Pendidikan Agama Islam, 2020)
Several centuries ago when humans were in the age of ignorance, Allah SWT sent His messenger by lowering the holy book to him, a book containing the guidelines for life that guide humans to the path of peace, which contains warnings and good news, in the first revelation clearly. Al-Qur'an explains with the word